2000
DOI: 10.4049/jimmunol.165.2.1074
|View full text |Cite
|
Sign up to set email alerts
|

Latent Murine γ-Herpesvirus Infection Is Established in Activated B Cells, Dendritic Cells, and Macrophages

Abstract: Intranasal infection of mice with the murine γ-herpesvirus MHV-68 results in an acute lytic infection in the lung, followed by the establishment of lifelong latency. Development of an infectious mononucleosis-like syndrome correlates with the establishment of latency and is characterized by splenomegaly and the appearance of activated CD8+ T cells in the peripheral blood. Interestingly, a large population of activated CD8+ T cells in the peripheral blood expresses the Vβ4+ element in their TCR. In this report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
296
3
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 278 publications
(322 citation statements)
references
References 47 publications
22
296
3
1
Order By: Relevance
“…2-4) raised the possibility that SAP-associated effects on B cell activation caused a deficiency in the normal reservoir for the establishment of latency. We have previously shown that B cell latency is established preferentially in activated germinal center B cells (15). However, full maturation to germinal center cells is apparently not required, as we have also previously reported that latency can be efficiently established in PNA high activated B cells from CD28-deficient mice, which, like SAP-deficient mice, have a deficiency in germinal center development (17).…”
Section: The Frequency Of Viral Latency In Activated Pna High B Cellsmentioning
confidence: 79%
See 2 more Smart Citations
“…2-4) raised the possibility that SAP-associated effects on B cell activation caused a deficiency in the normal reservoir for the establishment of latency. We have previously shown that B cell latency is established preferentially in activated germinal center B cells (15). However, full maturation to germinal center cells is apparently not required, as we have also previously reported that latency can be efficiently established in PNA high activated B cells from CD28-deficient mice, which, like SAP-deficient mice, have a deficiency in germinal center development (17).…”
Section: The Frequency Of Viral Latency In Activated Pna High B Cellsmentioning
confidence: 79%
“…Although germinal center cells are the preferential reservoir for the establishment of latency in wild-type mice (15), they are apparently not an absolute requirement, and latency can be efficiently established in highly activated B cells. For example, we previously showed that latency was efficiently established in CD28-deficient mice, which are defective in the ability to form germinal centers (15,17). In addition, in mixed bone marrow chimeric mice, latency was established comparably in CD40 ϩ and CD40 Ϫ B cells, despite the inability of CD40 Ϫ B cells to localize into germinal centers (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible explanation for differential infectivity is that the presence of BAC sequences in the ORF6 STOP virus may have resulted in an inability to establish latency in the spleen, as our studies comparing infections with ORF31STOP with and without BAC sequences revealed striking differences in the cellular reservoirs of latency. Removal of BAC sequences was associated with the establishment of latency in splenic B cells, macrophages, and dendritic cells, the previouslyidentified cellular reservoirs of early latency in the spleen following infection with wild-type ␥HV68 (30,31,34), whereas the presence of BAC sequences resulted in latency largely restricted to B cells (Table I).…”
Section: Discussionmentioning
confidence: 92%
“…It has been previously shown that latency in the spleen is established in B cells, macrophages, and dendritic cells (30,31), and is preferentially maintained in class-switched memory and germinal center B cells (32)(33)(34). To further characterize infection by ORF31STOP and to determine the impact of BAC sequences, we assessed which cell types harbored viral genome at early and late time points after i.p.…”
Section: Latency Is Established and Maintained In Splenic B Cells Folmentioning
confidence: 99%